2017
DOI: 10.1007/s00464-017-5623-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of laparoscopic graspers with enhanced haptic feedback on applied forces: a randomized comparison with conventional graspers

Abstract: BackgroundHaptic feedback, which enables surgeons to perceive information on interaction forces between instrument and tissue, is deficient in laparoscopic surgery. This information, however, is essential for accurate tissue manipulation and recognition of tissue consistencies. To this end, a laparoscopic grasper with enhanced haptic feedback has been developed: the force reflecting operation instrument (FROI). This study tested the effects of enhanced haptic feedback on force control, tissue consistency inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 34 publications
0
42
0
Order By: Relevance
“…A study showed that enhanced haptic feedback may reduce the interaction force between instrument and tissues during surgery. Therefore, this may lead to less tissue damage, fewer complications, shorter operation times, and improved ergonomics [36].…”
Section: Optigrip™ (Endoscopic Force-reflecting Instruments Bv Malmentioning
confidence: 99%
“…A study showed that enhanced haptic feedback may reduce the interaction force between instrument and tissues during surgery. Therefore, this may lead to less tissue damage, fewer complications, shorter operation times, and improved ergonomics [36].…”
Section: Optigrip™ (Endoscopic Force-reflecting Instruments Bv Malmentioning
confidence: 99%
“…Virtual-reality-based simulators offer objective feedback, which often correlates positively with patient-related outcomes, and different case scenarios (Brydges et al, 2015 ). However, they often lack realistic haptic feedback which is key in improving laparoscopic skills of the trainee (Pinzon et al, 2016 ; Alleblas et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“… 10 Reduced haptic feedback leads to grasping and tearing of tissue with excessive force. 11 Which in turn causes tissue damage and more complications. Henceforth, force reflecting operative instruments (FROIs) have been developed to increase haptic feedback during laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%